IMPLEMENTASI KONSEP KEPEMIMPINAN ADIL DALAM LEMBAGA ISLAM: STUDI PUSTAKA ATAS PRINSIP ‘ADL DALAM KHAZANAH KEPEMIMPINAN ISLAM - Prasetyowati, Firda (Jurnal Manajemen Pendidikan, 2025)
Leadership is a crucial element in shaping the governance of Islamic educational institutions that are both high-quality and integrity-based. From an Islamic perspective, leadership is not only assessed through administrative competence but also through moral and spiritual dimensions rooted in Sharia principles. One of the main principles is justice (‘adl), which requires leaders to act objectively, transparently, and responsibly in decision- making and human resource management. This research is a literature study aimed at exploring and analyzing the concept of just leadership in classical and contemporary Islamic literature, as well as examining its application in the context of Islamic educational institutions. The findings indicate that leadership based on the value of ‘adl fosters an inclusive work climate, enhances participation, strengthens teacher loyalty, and contributes to the improvement of graduate quality. The integration of the values of trust (amanah), consultation (shura), and justice (‘adl) forms a model of Islamic leadership that is both transformational and spiritual. Therefore, this study recommends the internalization of the principle of justice into the vision, strategies, and policies of Islamic educational institutions as a fundamental pillar in addressing global challenges.